Pengembangan Sistem Informasi Administrasi Keuangan Sekolah (Studi Kasus: MTS Yanuris 1 Linggapura) - Reza Faridh Mashyuri; Faizatul Amalia; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
School financial administration information system is a system that regulates the examination, management, control, search, and storage of school financial data. MTs Yanuris 1 Linggapura is a private school located in the Brebes Regency, where the management of school financial data is handled by the school treasurer include the management of school expenditure and income funds, the management of teacher honorariums, and the recapitulation of the payments of Contribution to Education Development (SPP) money. Some problems were found in the process of managing financial data, including inefficient report preparation, and report filing system, which is still in the form of paper that makes it possible for data loss. Based on the existing problems, therefore, a web-based application was made to reduce the time in preparing a report. System development at MTs Yanuris 1 Linggapura school uses the prototyping method. The system development process includes the stages of requirements analysis, implementation, and testing. The stage of requirements analysis gained 154 functional requirements obtained from 2 times of iterations at the prototyping stage. The stage of implementation uses the PHP programming language in the CodeIgniter framework. The stage of testing includes functional and non-functional testing. Functional testing includes unit testing that successfully carried out the test path based on 3 test cases, integration testing resulted valid status and validation testing resulted 100% valid from 234 test cases. Non-functional testing using usability and compatibility with system results is acceptable to the user and can run well on the Google Chrome browser version 77.